Tinjauan Hukum Islam terhadap TransaksiJual Beli dengan Sistem Barter Baje di Kecamatan Panca Lautang Kabupaten Sidrap - Rusmi, Rusmi; Badruzzaman; Sunuwati (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2022)
Sale and purchase transactions with a barter system are still being carried out in the Panca Lautang District, Sidrap Regency. In the transaction, during the harvest season, the baje seller visits the farmers who are harvesting to exchange rice baje, peanut baje, kukubima, hemaviton, milk, jordan bread, and m+milk for grain. The problems contained in this thesis are about buying and selling transactions with a baje barter system in Panca Lautang District, Sidrap Regency, as well as a review of Islamic law on buying and selling transactions with a baje barter system in Panca Lautang District, Sidrap Regency. qualitative research using a normative approach. In collecting data, field observations, interviews and documentation methods were used, the data analysis used was qualitative analysis. Islam is because in the pillars of barter in the ijab qabul there is an element of unwillingness from one of the parties, namely the buyer or the owner of the grain who feels that the selling value of the grain is more expensive than the price of the exchanged baje, but they still carry it out because the baje seller does not leave the location if the transaction has not been carried out. And one of the barter conditions is not fulfilled, namely the conditions between the two parties who barter both need it, in this case when the owner of the grain is visited once they want to do a barter transaction because they need a baje for the harvest car employee, but if twice or more the seller of the clothes exchanges the sale of his clothes for grain, then the owner of the grain no longer needs the clothes.